Cross-sectional area reference values for high-resolution ultrasonography of the upper extremity nerves in healthy Asian adults - Bae, Dae Woong; An, Jae Young (Medicine (Baltimore), 2021)
In this study, multiple-site, cross-sectional area (CSA) reference values were established for major peripheral nerves, including small branches, in the upper extremity of a healthy Asian population.This study included 107 prospectively recruited age-matched, healthy subjects with a mean age of 46 years (range, 24-75 years). All subjects underwent standardized nerve conduction studies for the median, ulnar, peroneal, posterior tibial, and sural nerves. CSA was measured unilaterally at 21 sites of the median, ulnar, radial, posterior interosseous, superficial radial sensory, musculocutaneous, lateral antebrachial cutaneous, and medial antebrachial cutaneous nerves.According to their age, the subjects were assigned to the younger group (20-40 years, n = 40), the middle group (40-59 years, n = 40), and the older group (60-80 years, n = 27). The significant differences of CSA values between age groups were found only at certain sites, such as the median (wrist, P = .003), ulnar (medial epicondyle, P = .031; forearm, P = .022), radial (antecubital fossa, P = .037), and superficial radial sensory nerve (P = .028). The CSA significantly correlated with gender, height, weight, and body mass index.This study provides CSA reference values for nerves, including small sensory nerves in the upper extremity, which can be useful in the ultrasonographic investigation of various peripheral neuropathies in the upper extremity.